2021
DOI: 10.3233/ves-201574
|View full text |Cite
|
Sign up to set email alerts
|

Directional effects of whole-body spinning and visual flow in virtual reality on vagal neuromodulation

Abstract: BACKGROUND: Neural circuits allow whole-body yaw rotation to modulate vagal parasympathetic activity, which alters beat-to-beat variation in heart rate. The overall output of spinning direction, as well as vestibular-visual interactions on vagal activity still needs to be investigated. OBJECTIVE: This study investigated direction-dependent effects of visual and natural vestibular stimulation on two autonomic responses: heart rate variability (HRV) and pupil diameter. METHODS: Healthy human male subjects (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…With regard to comparing EEG studies, vestibular stimuli and visual stimuli used to induce motion sickness activates a vast array of different cortical areas in the brain [ 37 , 53 62 ]. Previous research has also found that certain movements of visual scenes inside VR can alter HRV [ 8 , 63 ]. Constant clockwise rotation of the visual environment has been found to inhibit cardiac parasympathetic activity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to comparing EEG studies, vestibular stimuli and visual stimuli used to induce motion sickness activates a vast array of different cortical areas in the brain [ 37 , 53 62 ]. Previous research has also found that certain movements of visual scenes inside VR can alter HRV [ 8 , 63 ]. Constant clockwise rotation of the visual environment has been found to inhibit cardiac parasympathetic activity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also found that certain movements of visual scenes inside VR can alter HRV [ 8 , 63 ]. Constant clockwise rotation of the visual environment has been found to inhibit cardiac parasympathetic activity [ 8 ]. Root mean square of successive differences of R-R intervals (RMSSD) and standard deviation of R-R intervals (SDRR), measures of parasympathetic activity, were also found to be decreased in forward visual movement compared to backward visual movement during VR immersion in a rollercoaster ride [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the fact that visual stimulus was able to modulate only the cardiac response, but not the arterial pressure, may indicate that the autonomic response is driven by the parasympathetic system. Accordingly, recent data demonstrates parasympathetic activation by visual rotation in healthy male subjects 34 .…”
Section: Discussionmentioning
confidence: 94%
“…The vestibular-autonomic reflexes encompass numerous pathways triggered by vestibular activation, resulting in changes in sympathetic or parasympathetic outflows [4,5 vestibular nucleus to the parabrachial complex [6], which sends projections to brainstem and forebrain areas integrating vestibular sensation and autonomic control, and cerebellar modulation of brainstem areas mediating autonomic output [1,[7][8][9][10][11][12][13]. Various sites within the cerebellum (anterior lobe, rostral posterior lobe, caudal posterior lobe-nodulus) demonstrate the ability to influence sympathetic and parasympathetic reflexes [14][15][16]17 && ]. The central vestibular sensation and autonomic control systems are highly interconnected and converge within the insular cortex.…”
Section: Vestibular System As a Modulator For Autonomic Responsesmentioning
confidence: 99%